2014
DOI: 10.1519/jsc.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Olympic Weightlifting and Plyometric Training With Children Provides Similar or Greater Performance Improvements Than Traditional Resistance Training

Abstract: A number of organizations recommend that advanced resistance training (RT) techniques can be implemented with children. The objective of this study was to evaluate the effectiveness of Olympic-style weightlifting (OWL), plyometrics, and traditional RT programs with children. Sixty-three children (10-12 years) were randomly allocated to a 12-week control OWL, plyometric, or traditional RT program. Pre- and post-training tests included body mass index (BMI), sum of skinfolds, countermovement jump (CMJ), horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 37 publications
6
89
0
7
Order By: Relevance
“…Slower, more deliberate movements of traditional RT would not be expected to provide optimal training adaptations for sprint measures that involve higher speed, stretch-shortening cycle (SSC) type activities. Again, similar findings were reported by Chaouachi et al (2014) who found that traditional RT provided superior training adaptations compared to both Olympic weight lifting and plyometric training for 5 and 20 meter sprints. However, Radnor et al (2017) reported contradictory results to the present meta-analysis with plyometric training and combined strength and plyometric training providing more positive responders than strength training alone for sprint velocity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Slower, more deliberate movements of traditional RT would not be expected to provide optimal training adaptations for sprint measures that involve higher speed, stretch-shortening cycle (SSC) type activities. Again, similar findings were reported by Chaouachi et al (2014) who found that traditional RT provided superior training adaptations compared to both Olympic weight lifting and plyometric training for 5 and 20 meter sprints. However, Radnor et al (2017) reported contradictory results to the present meta-analysis with plyometric training and combined strength and plyometric training providing more positive responders than strength training alone for sprint velocity.…”
Section: Discussionsupporting
confidence: 88%
“…Power training (e.g., plyometrics) can improve youth's ability to increase movement speed and power production (Behm et al, 2008). Chaouachi et al (2014) reported similar findings when they compared training programs that involved two types of power training (Olympic weight lifting and plyometric) and traditional RT. In accordance with the present review and the concept of training specificity, both plyometric and Olympic weight lifting in the Chaouachi study provided greater magnitude improvements in CMJ than traditional RT.…”
Section: Discussionmentioning
confidence: 76%
“…However, positive effects on jump performance after different training interventions and different exercises have been detected (2,8,(11)(12)(13)17,22,34,46,61,68). The different effectiveness of free-weight training compared with machine-based strength training has often been discussed (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, é requerida a coordenação de diversos músculos para a execução técnica a alta velocidade (Justice, 2008;Tysz, 2009 (Winchester et al, 2009) e seu impacto como método de treinamento em diferentes modalidades esportivas tem sido estudado (A., 2012; J. Carlock et al, 2004;Chaouachi et al, 2014;L. Z. F. Chiu, Wagner, & Salem, 2006;Fry, A.C., 1991;Justice, 2008;Takano, 2013).…”
Section: O Power Snatchunclassified
“…Isto justifica que seja praticado por diferentes modalidades esportivas e utilizado no treinamento para aumentar a potência muscular. Como (Haycraft 2015) na natação, (Hori, Newton et al 2007) no football Australiano, salto vertical (Chiu, Wagner et al 2006), em velocistas de 100 e 200 metros (Hori, Newton et al 2008), no voleibol (Holmberg 2013) e até em aplicações com crianças de 12-13 anos (Chaouachi, Hammami et al 2014).…”
Section: O Power Snatchunclassified